Occupant behaviour as a fourth driver of fuel poverty (aka warmth & energy deprivation). (June 2019) - Kearns, Ade; Whitley, Elise; Curl, Angela
Abstract: A conceptual framework for occupant behaviour as a driver of fuel poverty is presented, comprising: housing and use of the home; heating and energy arrangements and thermal comfort; household structure and dynamics; health and well-being; household finances; and social activity and relations. This framework informs longitudinal analysis of movements into and out of fuel poverty among households in deprived communities in Glasgow. Household surveys across ten years yielded a longitudinal sample of 3297 cases where initial and subsequent fuel poverty status was recorded using an experiential measure. A third of households changed their fuel poverty status over time: 18% moving out of fuel poverty and 16% moving in. Factors strongly associated with movements into fuel poverty included: being a single parent (OR 2.27); experiencing a mental health problem (OR 2.74); and remaining out of work (OR 1.89). Movement out of fuel poverty was less likely among those with infrequent family contact (OR 0.55) and who moved home (OR 0.66); home improvements had no effect upon the experience of fuel poverty. It is argued that the policy problem should be considered one of 'warmth and energy deprivation', accompanied by a broader interpretation of vulnerability to as well as from fuel poverty. Highlights: Fuel payment difficulties are lower than official fuel poverty rates. People with mental health problems are more likely to enter fuel poverty. Family support networks are protective against fuel poverty. Higher standards of energy efficiency may be required from interventions. Wider efforts are needed to identify those at risk of warmth and energy deprivation.